We three queens [large type] - Bowen, Rhys (Bowen, Rhys. Royal Spyness mysteries, 2024)
"It's late 1936, and King Edward is in turmoil, having fallen in love with the scandalous Wallis Simpson. He wants to marry her but knows that doing so will jeopardize his crown. Edward confides in his dear friend Darcy, Georgie's husband, and the couple agree to hide Wallis in their home while Edward figures out what to do. But unbeknownst to Georgie and Darcy, Sir Hubert, the owner of the estate, has given a film crew permission to shoot a motion picture about on the grounds. When one of the stars of the film is found murdered on set, Georgie must solve the crime for king and country before scandal threatens to envelop them all"--